Time-variation in the relationship between white precious metals and inflation: A cross-country analysis - Vigne, Samuel (My University, 2018)
In recent years, as a result of an increasing financialisation of financial markets, white precious metals have slowly transformed from mere production inputs to investment assets. In order to analyse the characteristics of white precious metals and the consequences of the transition, this paper examines the long-run inflation hedging effectiveness of silver, platinum, and palladium using both linear and non-linear cointegration relationship procedures. This study is the first to formally investigate the inflation hedging effectiveness of white precious metals across different countries. Overall, the results point towards the superiority of palladium as the most reliable inflation hedge. Furthermore, country-specific graphical evidence uncovers time-variation in the inflation hedging potential of white precious metals.
PUBLISHED
Keywords: White precious metals; Silver; Platinum; Palladium; Inflation; Hedge